Investment Behaviour of Nepalese Investors - Adhikari, Pragya (PYC Nepal Journal of Management, 2010)
This article deals with the field that has been recently getting lots of attention from finance academics – investor behaviour. This article aims to explore why Nepalese investors’ invest in share markets and whether their decisions to invest in share market are in a way influenced by behavioural factors. The existence or otherwise of three selected behavioural biases, namely heuristics relating to information, herding behaviour and overconfidence were empirically tested through data collected from self-administered questionnaires from Nepalese investors and supplemented by interviews with brokers. Based on the analysis of findings, it is observed that Nepalese investors invested in shares for both financial and non-financial reasons. Behavioural factors have an important influence in Nepalese investors’ investment decision making process. Investors are found to exhibit some facets, all three selected behavioural biases, which are influencing their investment decisions.